Enhancing Al-Quran Reading Proficiency in Higher Education: The implementation of the Focused Mad & Idgham Technique - Muhd Syahazizamir, Sahmat; Fatin Ardani, Zamri (UNIMAS Publisher, 2024)
The issue of students' weakness in Quranic reading has long been a concern in Islamic education, and it continues to persist. This study aims to innovate Quranic teaching techniques by focusing on Mad (elongation) and Idgham (merging) rules. The study examines students' motivation and involvement in Quranic reading activities and investigates their learning experiences. Twenty-nine Year 1 students and 22 students from the Islamic Education Programme, performing at medium and low levels, were selected to participate in the intervention. Data were collected and analysed by observing the students' Quranic recitations and reactions. The researcher introduced the Focused Mad (elongation) and Idgham (merging) technique (FMI) as a solution for improving Quranic reading. The findings revealed that some students in the Islamic education program still read the Quran at a less than satisfactory level. However, it was observed that students could read the Quran more effectively using the FMI technique as an intervention. The findings also indicated that the FMI technique can increase the motivation and involvement of learners in reading the Quran. Additionally, the positive perception of the FMI technique among students suggests its potential to enhance their learning experience in Quranic education, fostering engagement, comprehension, and confidence in Quranic recitation. Overall, the Focused Mad (elongation) and Idgham (merging) Technique (FMI) not only improves the ability to read the Quran but also boosts students' confidence and involvement in learning the Quran.